GHz magnetic field influence on magnetization reversal in amorphous microwires. Issue 5 (10th April 2014) - Chizhik, A.; Ipatov, M.; Stupakiewicz, A.; Zhukov, A.; Maziewski, A.; Gonzalez, J.
Abstract: This work is devoted to the study of the magnetization reversal in the Co‐rich glass covered microwire with nearly‐zero magnetostriction in the presence of super high frequency (SHF) (about 1 GHz) circular magnetic field that is important for the elucidation of GMI mechanism. Magnetic domain imaging has been performed by means of magneto‐optical Kerr effect (MOKE) polarizing microscopy. Local hysteresis loops were obtained from the magneto‐optic intensity as a result of images processing. The increase of the SHF field amplitude causes the change of the magnetization reversal mechanism – the rotation of the magnetization dominates. Also the hysteresis loop has an asymmetric shape that confirms the competition between stable and meta‐stable helical magnetic states. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)